How much has people empowerment progressed among small farmers and fisherfolk? State of people's organizations in the Philippines - Danilo A. Songco (Philippine Institute for Development Studies (PIDS), 2022)
This is an attempt to quantify government's performance in empowering small farmers and fishers following the provisions of AFMA. It establishes four dimensions of empowerment that may be used to measure empowerment and presents some evidence of how government has performed under each of these dimensions. It concludes that government has been on track in following AFMA's prescriptions for SFF empowerment but that its efforts are coming too little, too late although there are strong indications that such effort can be upscaled and can still achieve the empowerment objectives of AFMA if the government can undertake certain shortterm and long-term policy measures.
Keywords: 330; empowerment of small farmers and fishers; access to public resources; organizing capability; voice in policymaking; economic well-being; pursue F2C2 program; management capability of agricoops; inter-agency collaboration in empowering SFF; commercialization of small farms; agricultural cooperatives law; developing the youth in agriculture